Investigation of characteristics of non-simultaneous arc discharge in titanium vapors in glow discharge electron evaporators - Denbnovetskiy, S.V.; Melnyk, V.I.; Melnyk, I.V.; Tugay, B.A.; Porytskyy, P.V. (Вопросы атомной науки и техники, 2007)
Investigations of simultaneous applying of high voltage glow discharge (HVGD) and non-self-maintained low-pressure arc discharge for obtaining high-quality titanium nitride coatings are provided. Obtained results are compared with experiments, provided on experimental technological equipment. Provided investigations showed, that using of glow discharge electron guns (GDEG) in installations for obtaining of chemically-complex compounds with plasma activation lead to simplifying of technological equipment and to improving the films quality. For investigated electrical parameters there are no necessary special technical measures for providing both HVGD and arc stability, early considered simple technical solutions are enough. Using of simple mechanical pumps for realizing binary films deposition in the range of operation pressure 10⁻² – 1 Pa with joint pumping of electron gun and technological chamber is also possible. Necessary technological equipment can be elaborated in correspondence with the customers’ requirement. Досліджується сумісне застосування високовольтного тліючого розряду (ВТР) та несамостійного вакуумно-дугового розряду низького тиску для отримання високоякісних покриттів із нітриду титана. Отримані теоретичні результати підтверджуються експериментами, проведеними на технологічному обладнанні. Проведені дослідження показали, що використання газорозрядних гармат в електронно-променевому обладнанні, призначеному для осадження хімічно складних покриттів та використання дугового розряду для активації плазми, дозволяють спростити електронно-променеве обладнання та поліпшити якість отримуваних покриттів. Исследуется совместное применение высоковольтного тлеющего разряда (ВТР) и несамостоятельного вакуумно-дугового разрядов низкого давления для получения высококачественных покрытий из нитрида титана. Полученные теоретические результаты подтверждаются экспериментами, проведенными на технологическом оборудовании. Проведенные исследования показали, что использование газоразрядных электронных пушек (ГРЭП) в электронно-лучевом оборудовании, предназначенном для нанесения покрытий сложного химического состава, совместно с использованием дугового разряда для активации плазмы, позволяет упростить электронно-лучевое оборудование и повысить качество получаемых покрытий.